TRANSFORMASI PERUMAHAN SOSIAL DAN KEBERLANJUTAN PERUMAHAN DI PERUMNAS SENDANGMULYO - Nany Yuliastuti; Annisa Mu’awanah Sukmawati (Diponegoro University, 2016)
Based on the reality on the ground with a variety of reasons and is, in a relatively short period has undergone a physical change by the wishes and needs of its owners. During its development, the house is not only seen from the quantitative aspect but also growing in terms of quality. In terms of its range tailored to the needs of, social, economic, institutional, as well as the development of the family concerned. Improved physical quality is usually directly proportional to the level of quality of life of its owner. In the framework of realization of self-actualization trigger, physical changes in the residential houses diverse forms/form and its range depends on the abilities, desires and needs of each family. The many activities uncontrolled housing physical development, particularly in the RS and related to the development and physical changes in the home that have an impact on environmental damage, so that its existence should receive special attention. This research takes object on the Housing Perumnas Sendangmulyo. The research conduct on 83 households in the sample of 497 households inhabit the object of research. The research methodology used the quantitative methodology and to obtain necessary data and information of the variables, this studies using questionnaire, interviews, and observations. Analysis techniques in the proof of linkages between variables using the method of cross tabulation and chi-square analysis, double regression and contingency coefficient correlation. The final results of this study is the identification of the level of quality of housing transformation that occur in the housing in the Perumnas housing and can be concluded that there are a link and influences between quality of life by physical changes in existing homes. The quality of housing, it means is related economic and social. Level of housing transformations that house is basically influenced by the level of income, education, family size and motivation of the owners of the house, while the types of jobs tend to have no effect on the physical changes in housing.